PENGARUH PENDIDIKAN KEWIRAUSAHAAN, MOTIVASI BERWIRAUSAHA, DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DI SMK NEGERI 9 JAKARTA - Latip, Nadia Salsabila; Eryanto, Henry; Usman, Osly (Transpublika Publisher, 2023)
This study aims to determine the influence of entrepreneurship education, entrepreneurial motivation, and family environment on entrepreneurial interest in SMK Negeri 9 West Jakarta. The population in this study is all class XI and XII students from five majors at SMKN 9 Jakarta. The sample in this study was 191 students, this number was obtained from calculations based on Isaac and Michael's table. Data collection in this study is primary data using questionnaires based on Likert scale. The analytical technique used in this study is Structural Equation Modelling with the Partial Least Square (SEM-PLS) model. The results of this study show: (1) there is a positive and significant direct influence of entrepreneurship education on entrepreneurial interest, (2) there is a positive and significant direct influence of entrepreneurial motivation on entrepreneurial interest, (3) there is a positive and significant direct influence the family environment on entrepreneurial interest.